EXPLORING THE PERCEPTION OF ACADEMIC FRAUD, ACADEMIC INTEGRITY ON THE BEHAVIOR OF ACCOUNTING STUDENTS IN UNIVERSITIES - Irlan Fery (Transpublika Publisher, 2024)
The aim of this research is to determine the perception of academic cheating and academic integrity and their impact on the behavior of accounting students in higher education. Academic fraud and academic integrity play a crucial role in shaping the character and professional ethics of accounting students, who will eventually become professionals. The research employs a quantitative approach, distributing questionnaires to Accounting majors at several universities in Palembang City. A total of 75 respondents participated, and the measuring tool used was multiple regression. The questionnaire was designed to gauge the level of perception regarding academic cheating, the level of academic integrity, and student behavior in dealing with academic pressure. The research results indicate a correlation between perceptions of academic cheating and the level of academic integrity. Students with a high perception of academic cheating tend to exhibit a lower level of academic integrity. Additionally, a relationship was found between academic integrity and student behavior in dealing with academic pressure. Students with a high level of academic integrity tend to approach academic pressure with a more ethical and responsible attitude.